Technical Feasibility Study and Design of 60 kWP On-Grid Solar Power Plant at Joint Lecture Building-5, University of Muhammadiyah Malang - Nabila Ayu Febrianti; Machmud Effendy; Basri Noor Cahyadi (Universitas Panca Marga, 2025)
The problem of dependence on fossil energy which has an impact on the energy crisis and the environment. The current renewable energy mix is still at 14% which is far from the 23% target in 2025, encouraging the need for the development of Solar Power Plants (SPP) as part of the New Renewable Energy (NRE) mix in Indonesia. This research aims to design an On-Grid Solar PV system with a capacity of 60 kWp at the Joint Lecture Building-5 (JLB) of Muhammadiyah University of Malang (UMM) and analyze the technical and economic feasibility. The methods used include electrical load survey, climate and radiation data collection, and system design simulation using PVsyst software. The simulation results show an annual Performance Ratio (PR) value of 0.839 with an annual energy production of 105,000 kWh. Energy production analysis shows stable system performance with total losses below 2 kWh/kWp/day. However, based on the economic analysis, the 20-year Net Present Value (NPV) is negative at - IDR 646,841,211, indicating the project is not financially viable without incentive support. Nonetheless, the project is considered technically feasible and can serve as a reference for the implementation of higher education-scale solar power plants.